2013
DOI: 10.1111/pbr.12032
|View full text |Cite
|
Sign up to set email alerts
|

Efficient application of in vitro anther culture for different European winter wheat (Triticum aestivum L.) breeding programmes

Abstract: The efficiency of our anther culture protocol was tested with high‐ and low‐responding genotypes, ‘Svilena’ and ‘Berengar’, and 93 F1 winter wheat crosses in 2010 and 2011. Based on data for these genotypes, the effect of genotype influenced the number of embryo‐like structures, regenerated plantlets and green plantlets, while the number of albino plantlets was affected by genotype, year and environmental factors. Although genotype also influenced the production of green plantlets from breeding crosses, with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
7
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 24 publications
5
69
7
2
Order By: Relevance
“…Genotype dependency and albinism limit the wide application of anther cultures in practical wheat breeding (Rybczyński et al, 1991;Marciniak et al, 2003;Broughton, 2011;Redha and Suleman, 2011;Lantos et al, 2013). In this study, the frequency of formation of embryo-like structure was shown to be influenced by the genetic background.…”
Section: Discussionmentioning
confidence: 58%
“…Genotype dependency and albinism limit the wide application of anther cultures in practical wheat breeding (Rybczyński et al, 1991;Marciniak et al, 2003;Broughton, 2011;Redha and Suleman, 2011;Lantos et al, 2013). In this study, the frequency of formation of embryo-like structure was shown to be influenced by the genetic background.…”
Section: Discussionmentioning
confidence: 58%
“…These genotypes are a promising source for breeding resistant varieties of acceptable yield capacity and could be of value for growing in organically oriented farming systems. For breeding using doubled haploids, it is essential to have an estimate of the anther culture responsiveness of the parental genotypes and the hybrid material (Lantos et al 2013). In our case, 'Svilena' is a highly responsive variety in terms of high rate of callus and embryoid induction, high rate of green plantlets regeneration and relatively low occurrence of albinism (Belchev et al 2000;Lantos et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For breeding using doubled haploids, it is essential to have an estimate of the anther culture responsiveness of the parental genotypes and the hybrid material (Lantos et al 2013). In our case, 'Svilena' is a highly responsive variety in terms of high rate of callus and embryoid induction, high rate of green plantlets regeneration and relatively low occurrence of albinism (Belchev et al 2000;Lantos et al 2013). This quality is expected to have been transferred in some of the 'Svilena'-derived DH lines.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ten anther Opsahl-Ferstad et al 1994b). One highly androgenic genotype from population 6 generated over 1500 green plants per 100 AC, which is comparable to yields of the responsive model barley cultivar 'Igri' (Jacquard et al 2006) but far better than 'Svilena', the model used in wheat (Lantos et al 2013). These high yields are probably due to the superior genetics of the studied plant material rather than the relatively minor differences between our method and previous practices (Olesen et al 1988;Opsahl-Ferstad et al 1994a, b).…”
Section: Androgenic Capacitymentioning
confidence: 93%